Development Module Practical Based Experiments in Basic Science Courses - Atika Anggraini; Ummiy Fauziyah Laili; Rizki Dwika Septiarini; Nia Ellia Malika; Arifin Saaf; Shahabuddin bin Hasyim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Basic Science learning requires practicum modules that facilitate systematic, structured, and learning-outcome-oriented experimental experiences. However, the modules used so far have not fully met the aspects of independent learning, clarity of work steps, and integration between concepts and practice. This study aims to develop experiment-based practicum modules for Basic Biology, Basic Physics, and Basic Chemistry using the 4D development model (Define, Design, Develop, and Disseminate). The development stage involved validation by five experts, namely experts in biology, physics, chemistry, media, and language, as well as student response tests. The data analysis method used in this study was descriptive quantitative analysis, involving calculating percentages of validation scores and student responses, which were then interpreted against predetermined validity criteria. The validation results showed a highly valid category across almost all aspects, with 88–93% in material validation, 88–95% in media validation, and 81% in student responses. The student response test involved 25 respondents, who were selected to assess the practicality and usability of the developed practicum module. Revisions were made based on validator input, such as improving image quality, refining language, and standardizing the practicum structure. Overall, the developed module was deemed feasible and effective as teaching material to support Basic Science practicum learning. This study also recommends further development through the integration of interactive digital media and trials on a larger scale. Keywords: development, experimental modules, basic science